KOMUNIKASI, KEPEMIMPINAN, DAN KINERJA PEGAWAI - Kiswanto, Riza Febrianty, Meyzi Heriyanto, (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Communication, Leadership, and Employee Performance. The purpose of this study was to analyze the influence of communication and leadership on employee performance at the Pekanbaru Regional Secretariat Office. The population in this study were all employees at the Regional Secretariat of Pekanbaru City who were taken in saturated sampling so that the study sample of 61 employees was obtained. The research variable uses two variables, namely the independent variable and the dependent variable. The dependent variable (y) in this study is employee performance. Independent variable (x) includes: communication (x1) and leadership (x2). This research is quantitative research. The method of data analysis uses multiple linear regression analysis. Processing data using the SPSS program for Windows Release 23.0. The results showed that partially the communication and leadership variables had an effect on the performance of employees at the Regional Secretariat of Pekanbaru City. The results of the analysis showed that communication had a more dominant influence than leadership on employee performance.